Diskursus Artis Menjadi Kaum Agamis Dalam Instagram - Fernando, Henky; Larasati, Yuniar Galuh; Jubba, Hasse; Cahyani, Novita (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
This study, in addition to describing the emergence of artists as religious people in Instagram social media, will also explain the discourse that emerged on this phenomenon. This study is a qualitative descriptive type using the netnography method. Data collection in this study was carried out through reading the Instagram social media posts of artists who were active and consistent in uploading religious posts. Therefore, the data in this study is in the form of a classification of the Instagram posts of artists with religious themes in the form of image formats. The analysis in this study uses thematic analysis by emphasizing the development of themes or topics in immersive inductive images. The findings in this study show that the emergence of artists as religious on Instagram social media is not slightly influenced by the identity and choice of the content displayed. The emergence of artists as religious people in Instagram social media has also brought up various kinds of evaluative discourses in the form of pro and contra attitudes from Instagram social media users. So the contestation of meaning in the Instagram posts of artists with the theme of religion is a very important context to be discussed by further studies.